Culinária popular: a sinalização de status na alta gastronomia no Brasil - Rossi, Bianca Nobre (2025)
This thesis investigates how status signaling strategies influence the valuation of popular cuisine in Brazilian haute gastronomy. Considering consumption as a mechanism of social distinction in a scenario of weakening class and status boundaries, we analyzed how haute cuisine restaurants in Brazil assimilate dishes, ingredients, and narratives associated with popular cuisine. The study is based on Signaling Theory, Convention Theory, and the Trickle Down Circle Theory to understand the processes of symbolic and market legitimation for this type of consumption. A qualitative, multi-methodological approach was adopted, based on four empirical studies: participant observation in an elite culinary school; technical visits to haute cuisine restaurants; qualitative interviews with chefs; and content analysis of specialized gastronomic media. The data were analyzed through theme coding and triangulation between sources. The results showed that the appreciation of popular cuisine in haute cuisine depends on the combination of multiple status signals, such as the chef's authorship, certifications, dish aesthetics, and appeals based on locality, sustainability, and authenticity. Ingredients and preparations traditionally associated with simplicity are reinterpreted as goods of high symbolic and economic value, especially when mediated by gastronomic media, which play a central role in legitimizing these practices and building symbolic hierarchies in the field of food consumption. As a contribution, the thesis expands the application of the theories to the Brazilian context, offering an integrated understanding of the dynamics of status attribution, consumption, and sustainability in gastronomy. Additionally, it contributes to marketing and consumption studies by highlighting how pro-social and environmental behaviors can operate as signals of distinction. This study contributes to the following Sustainable Development Goals: SDG 8 - Decent work and economic growth (8.2 and 8.9); SDG 9 - Industry, innovation and infrastructure.